DESIGNING ILLUSTRATIONS FOR A TRADING CARD GAME BASED ON NUSANTARA CHARACTERS TO PROMOTE THE CULTURAL RICHNESS OF NUSANTARA - Yasid, Muhammad Zhafran; Fiyanto, Arif (LPPM Univ. Ibn Khaldun Bogor, 2025)
This article discusses the process of designing illustrations for a Trading Card Game (TCG) concept titled Myth Warriors, which features the theme of Nusantara mythology. The purpose of this work is to create an entertainment medium that simultaneously introduces the cultural richness of Indonesia through the visualization of local mythological characters. Using a qualitative descriptive method, the author conducted observations to adapt mythological characters into illustrations and visual identities that are appealing to children and teenagers. The design results demonstrate that the combination of cultural elements and modern visual styles can serve as an effective educational and entertainment tool. Through this project, it is hoped that the Myth Warriors card game design can become an alternative medium that combines entertainment and cultural education, and contribute to the preservation of local culture through a creative and relevant visual approach for the current generation.